Effect of Medium Chain Fatty Acid Supplementation on Nursery Pig Fecal Microbial Populations - J. T. Gebhardt; M. C. Niederwerder; S. C. Fernando; W. Abbas; T. E. Burkey; K. A. Thomson; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 360 pigs [DNA (Columbus, NE) 400 × 200; initially = 14.8 ± 0.15 lb] were used to evaluate the effects of dietary medium chain fatty acid (MCFA) addition on fecal microbial populations. Upon arrival at the nursery, pigs were randomized to pens (5 pigs per pen) and allowed a 6-d acclimation period, at which point pens of pigs were blocked by body weight (BW) and randomized to dietary treatment (9 pens per treatment). Medium chain fatty acids (Sigma Aldrich, St. Louis, MO) included hexanoic (C6), octanoic (C8), and decanoic (C10), and were guaranteed ≥ 98% purity. Treatment diets were formulated to meet or exceed NRC requirements for 15- to 25-lb pigs. Fecal samples were collected from pigs fed control and 1.5% MCFA blend (1:1:1 ratio C6, C8, and C10) diets on d 0 and d 14 and analyzed using 16s rDNA sequencing. A total of 6 phyla were identified with ≥ 1% relative abundance for at least one of the treatment × day analysis combinations. The largest proportion of relative abundance on a phyla level on d 14 consisted of Firmicutes (54% control, 44% MCFA) and Bacteroidetes (32% control, 43% MCFA). A marginally significant treatment × day interaction was observed in the Proteobacteria phylum (P= 0.080), where relative abundance did not change over time in pigs fed the control diet (P= 0.848), whereas a marginally significant decrease over time was observed in pigs fed the MCFA diet (P= 0.092). There was no evidence of an effect of MCFA addition over time for the relative abundance of the remaining phyla (treatment × day,P≥ 0.359). The main effect of day indicated a significant increase over time in the Tenericutes phylum (P= 0.008) and a significant decrease over time in the Proteobacteria (P= 0.017) and Spirochaetes phyla (P= 0.020). A Firmicutes:Bacteroidetes ratio was calculated, and there was no evidence of a treatment × day interaction (P= 0.338) or day effect (P= 0.211). A total of 23 microbial families were detected at ≥ 1% relative abundance for at least one of the treatment × day analysis combinations. The families with the greatest relative abundance were Prevotellaceae, Ruminococcaceae, and S24-7 families, which had ≥ 10% relative abundance for at least one of the treatment × day analysis combinations. There was no evidence of an effect of MCFA addition over time on the relative abundance for any family (treatment × day,P≥ 0.123). For both treatments, a reduction over time was observed for Ruminococcaceae (P= 0.048), Lachnospiraceae (P= 0.004), Christensenellaceae (P= 0.004), Spirochaetaceae (P= 0.029), Bacteroidaceae (P= 0.010), and Succinivibrionaceae (P= 0.029) families. An increase in relative abundance over time was observed for the unclassified Clostridiales (P= 0.019), Clostridiaceae (P<0.001), unclassified RF39 (P= 0.008), and Clostridiales; and other (P<0.001) families. No evidence of a difference in alpha diversity was observed for either Chao1 (estimate of species richness) or observed operational taxonomic units (OTUs). In summary, adding 1.5% MCFA blend in swine nursery diets did not appear to significantly alter the composition of fecal microbial populations compared to a control diet using 16s rDNA sequencing analysis. Changes in microbial populations were observed over time with both treatments. Further investigation into the mechanism by which MCFA addition benefits growth performance is necessary. Moreover, additional studies into understanding the interactions between MCFA and the gastrointestinal microbiome are warranted due to its well-known inactivation effects on selected microbes.
Keywords: medium chain fatty acid; microbiome; nursery pigs